2018
DOI: 10.1242/jcs.213686
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional protein secretion – new insights into the pathogenesis and therapeutic targets of human diseases

Abstract: Most secretory proteins travel through a well-documented conventional secretion pathway involving the endoplasmic reticulum (ER) and the Golgi complex. However, recently, it has been shown that a significant number of proteins reach the plasma membrane or extracellular space via unconventional routes. Unconventional protein secretion (UPS) can be divided into two types: (i) the extracellular secretion of cytosolic proteins that do not bear a signal peptide (i.e. leaderless proteins) and (ii) the cell-surface t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
102
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(106 citation statements)
references
References 158 publications
2
102
0
2
Order By: Relevance
“…These potential roles for Lon protease in the extracellular environment are very intriguing and warrant further study. Moreover, our detection of proteins undergoing both conventional (e.g., signal peptide, transmembrane domain) and non-conventional (e.g., membrane-associated, guilt-by-association) modes of secretion, along with overlap between the secretome and OMV profiles, and the presence of proteases in extracellular bacterial vesicles further supports the presence of Lon protease in the extracellular environment (Dalbey et al, 2012;Lee et al, 2012;Cezairliyan and Ausubel, 2017;Kim et al, 2018). We also compare the abundance profiles of vesicle-associated K. pneumoniae proteins and observe an overall increase in vesicle-associated proteins under limited vs. replete iron conditions.…”
Section: Discussionsupporting
confidence: 59%
“…These potential roles for Lon protease in the extracellular environment are very intriguing and warrant further study. Moreover, our detection of proteins undergoing both conventional (e.g., signal peptide, transmembrane domain) and non-conventional (e.g., membrane-associated, guilt-by-association) modes of secretion, along with overlap between the secretome and OMV profiles, and the presence of proteases in extracellular bacterial vesicles further supports the presence of Lon protease in the extracellular environment (Dalbey et al, 2012;Lee et al, 2012;Cezairliyan and Ausubel, 2017;Kim et al, 2018). We also compare the abundance profiles of vesicle-associated K. pneumoniae proteins and observe an overall increase in vesicle-associated proteins under limited vs. replete iron conditions.…”
Section: Discussionsupporting
confidence: 59%
“…In our research, no additional vesicular structures were observed during microscopy. In mammalian cells and yeast, several examples of LPs were described to be secreted through plasma membrane pore formation or by ABC transporters anchored in the plasma membrane, such as, e.g., described for interleukin (IL)-1β, fibroblast growth factors, and the HIV transactivator of transcription [44]. In plants, direct translocation across the plasma membrane was not discovered yet.…”
Section: Discussionmentioning
confidence: 99%
“…Cells can utilize various unconventional secretory mechanisms to release proteins . There is now growing evidence that unconventional secretory routes can markedly contribute to the presence of intracellular proteins in the extracellular space (e.g., annexins, ANXAs; heat shock protein 70, HSP70; interleukin 1‐beta, IL‐1ß) . Thus, it seems reasonable that Oecs release specific proteins like HSPs via unconventional mechanisms.…”
Section: Discussionmentioning
confidence: 99%